2021
DOI: 10.3390/brainsci12010052
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity after Intermittent Hypoxic Brain Condition in Rats

Abstract: Hypoxic brain injury is accompanied by a decrease in various functions. It is also known that obstructive sleep apnea (OSA) can cause hypoxic brain injury. This study aimed to produce a model of an intermittent hypoxic brain condition in rats and determine the activity of the brain according to the duration of hypoxic exposure. Forty male Sprague–Dawley rats were divided into four groups: the control group (n = 10), the 2 h per day hypoxia exposure group (n = 10), the 4 h per day hypoxia exposure group (n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Abu et al found that tissue inhibitor of matrix metalloproteinase-3 (TIMP-3) (an efficient inhibitor of several members of the ADAM and ADAMTS) had powerful regulatory effects on anti-inflammatory and antiangiogenic activities [ 48 ]. Meanwhile, OSA is associated with angiogenesis [ 49 ]. Mun et al revealed that rats with an intermittent hypoxic brain condition stimulated vascular proliferation for spontaneous recovery through VEGF elevation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abu et al found that tissue inhibitor of matrix metalloproteinase-3 (TIMP-3) (an efficient inhibitor of several members of the ADAM and ADAMTS) had powerful regulatory effects on anti-inflammatory and antiangiogenic activities [ 48 ]. Meanwhile, OSA is associated with angiogenesis [ 49 ]. Mun et al revealed that rats with an intermittent hypoxic brain condition stimulated vascular proliferation for spontaneous recovery through VEGF elevation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, OSA is associated with angiogenesis [ 49 ]. Mun et al revealed that rats with an intermittent hypoxic brain condition stimulated vascular proliferation for spontaneous recovery through VEGF elevation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The humidity was measured and maintained at 40–50% by circulating gas through the freezer and using silica gel. The ambient temperature was kept at 22–24 °C [ 19 ].…”
Section: Methodsmentioning
confidence: 99%